'Give me neither wealth nor poverty but appoint for me what is necessary and sufficient' (Proverbs 30:8 LXX): But Necessary for What and Sufficient for What?. (May 2022) - Jones, John D.
For the Life of the World ( FLW ), part IV, offers a thought-provoking discussion about the problems of poverty, wealth and civil justice. Poverty, basic needs and a living wage are central to the concerns and proposed goals for action in this part. While understandably referred to in a general sense since FLW is 'a preliminary step for further discussion', in the contemporary world, these issues are highly ambiguous, controversial and difficult to measure. Hence, to promote further dialogue, I explore and highlight critical issues that must be addressed. I also offer a brief discussion of the stigmatization of poverty that cruelly affects many who are poor. I argue that to develop a more expansive theological and normative discourse about poverty and wealth, we should first aim to clearly understand key terms such as poverty in a fully multidimensional, holistic manner that explicitly considers the dynamics of the stigmatization of poverty.